Development of a Health Promotion Application on Cancer Survivorship as an Educational Content for Nursing Students - Yoonhee Seok; Eunyoung E. Suh (Elsevier, 2022)
Summary: Purpose: This study aimed to develop a health promotion application for cancer survivorship (CS app) based on the adult learning and self-efficacy theories and evaluated its usability as an educational tool for nursing students. Methods: The CS app was developed according to ADDIE (analysis, design, development, implementation, and evaluation) model. It consisted of interventions involving medication, diet, exercise, stress management, symptom management, and regular medical checkup for cancer survivors on three different levels in terms of difficulty and complexity. It was designed to teach nursing students how to provide tailored care to cancer survivors as well as help survivors with their repetitive and regular health management. The Mobile App Rating Scale and the user version of the Mobile App Rating Scale were used for a heuristic evaluation of the CS app by the experts and student users. Results: The CS app was developed based on literature reviews and cancer survivorship guidelines. It was evaluated by 20 student users and five experts based on a 5-point scale and obtained a score of 3.97 and 3.66, respectively. Nursing students rated the CS app positively, mentioning that they were able to "learn about appropriate nursing interventions for patients in various cases" and that they became interested in caring cancer survivors' health using the CS app. Conclusions: The CS app is an effective and user-friendly educational tool to increase the motivation of nursing students in learning cancer survivorship care. This highlights the potential of CS app as a useful learning tool for nursing students.